Bank Health Analysis with RGEC Method Case Study of Bank Tabungan Negara (BTN) - Sintia Deliana Putri; Endang Kartini Panggiarti; Chaidir Iswanaji (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
The banking sector is one of the important components in the economy because one of the functions is collecting public funds. In collecting public funds, banks must have a good and trustworthy reputation. Therefore, banks are required to be able to achieve and maintain good levels of performance, because good levels of bank performance can increase the trust and loyalty of customers and people to use financial products, services and activities from the bank. The performance of a bank is reflected in the financial statements, can also be reflected through published earnings. Bank health is also reflected in the performance of a bank, because health assessments are recorded in published financial statements. Bank health is very important because a healthy bank will be able to carry out its normal operational activities. In addition, bank health is needed so that public confidence in the banking industry in terms of saving funds is maintained with banking regulations. This study aims to determine the Bank Health of Bank Tabungan Negara using the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) methods. The data used in this study are 2017-2019 Annual Report. The results of this study show that the health of banks in 2017 and 2018 was declared healthy, while in 2019 it was declared quite healthy.